Dyslipidemia as risk factor for cerebrovascular disease: Case-control study - Castillo Castillo, Juan Lorgio (2016)
Objetive: To determine whether dyslipidemia is an independent risk factor for cerebrovascular disease. Material and methods: A case-matched controls by age and sex was performed. The cases were composed of patients with clinical and tomographic diagnosis of cerebrovascular disease and controls for patients with different disease. Both groups underwent dosage serum total cholesterol, LDL cholesterol and triglycerides in the first 24 hours of admission to hospital. Results: A total of 160 patients were studied (80 cases and 80 controls). The average for cases was 64.92 ± 11. 58 years and 64.97 ± 11.42 years controls; 63.75% were of male and 36.25% females (p = 0.798, not significant). Mean serum cholesterol, triglycerides and LDL cholesterol in the cases were 191.4, 130.50 and 120.41 mg / dl; with p = 0.008, 0.001 and 0.060 in cases and controls respectively. The odds ratio between cases and controls demonstrated that dyslipidemia does not increase the risk for cerebrovascular disease (OR: 0.308). Conclusion: dyslipidemia is not an independent risk factor for cerebrovascular disease.